2011
DOI: 10.1039/c1jm14785d
|View full text |Cite
|
Sign up to set email alerts
|

Vapor treatment of nanocrystalline WO3 photoanodes for enhanced photoelectrochemical performance in the decomposition of water

Abstract: WO 3 mesoporous films were prepared using a sol-gel method to serve as the photoanode for water cleavage in a 1 M HClO 4 solution with Pt as the counter electrode. Post-treatment of the as-synthesized WO 3 film with methanol and ethanol vapors, especially with methanol, improves the photocurrent during photoelectrolysis of water. Water and hexane vapors have a deleterious influence on the WO 3 film. Scanning electron microscopy and X-ray diffraction analyses showed that treatment with methanol vapors did not a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 52 publications
(61 reference statements)
2
28
0
Order By: Relevance
“…The observed onsets of +1.85 V vs RHE for water oxidation, which agrees with the literature value of +1.9 V for a pristine monoclinic WO 3 film, 14,18,37,39 remain independent on the electrochemical reduction treatment. The groups of Lewis 43 and Choi, 44 recently reported that water oxidation is occurring in competition with sulfate oxidation at the illuminated WO 3 surface.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…The observed onsets of +1.85 V vs RHE for water oxidation, which agrees with the literature value of +1.9 V for a pristine monoclinic WO 3 film, 14,18,37,39 remain independent on the electrochemical reduction treatment. The groups of Lewis 43 and Choi, 44 recently reported that water oxidation is occurring in competition with sulfate oxidation at the illuminated WO 3 surface.…”
Section: Resultssupporting
confidence: 80%
“…An indirect bandgap of 2.6 eV and a direct bandgap of 2.9 eV are observed, in good agreement with the literature values reported for monoclinic WO 3 . 38,39 Besides, an additional broad absorption peak in the infrared region is observed and is attributed to the electron transfer from W 6+ to W 5+ at the oxygendeficient sites in the structure. 10 This oxygen deficiency makes WO 3 nonstoichiometric and intrinsically n-type.…”
Section: Resultsmentioning
confidence: 98%
“…Solvent treatment of WO 3 films (thickness about 4 µm) pre pared by sol-gel resulted as well useful in enhancing the photo electrochemical performances: [168] while not influencing the mesoscopic structure of the films, vapor treatments resulted in deterioration of the WO 3 nanocrystalline framework. Methanol treated samples, in particular, exhibited enhanced photocur rent, attributed to suppression of interfacial recombination of photogenerated electrons.…”
Section: Tungsten Trioxidementioning
confidence: 99%
“…At the same time, the photocurrent values of WO3 and HfO2/WO3 decrease 29.0% (from 0.81 to 0.57 mA/cm 2 ) and 24.4% (from 0.94 to 0.71 mA/cm 2 ), respectively, after irradiation of 1180 s. This indicates that the HfO2/WO3 film shows better stability compared to the bare WO3 film. The photoelectrochemical performances of both photoanodes are also estimated by the light energy to chemical energy efficiency, which is calculated with the following equation [31,32].…”
Section: Characterization Of the As-prepared Filmsmentioning
confidence: 99%